Influence of fault reactivation during multiphase rifting: The Oseberg area, northern North Sea rift. (September 2017) - Deng, Chao; Fossen, Haakon; Gawthorpe, Robert L.; Rotevatn, Atle; Jackson, Christopher A-L.; FazliKhani, Hamed
Abstract: Multiphase rifts tend to produce fault populations that evolve by the formation of new faults and reactivation of earlier faults. The resulting fault patterns tend to be complex and difficult to decipher. In this work we use seismic reflection data to examine the evolution of a normal fault network in the Oseberg Fault Block in the northern North Sea Rift System – a rift system that experienced Permian – Early Triassic and Middle Jurassic – Early Cretaceous rifting and exhibits N-S, NW-SE and NE-SW oriented faults. Both N-S- and NW-SE-striking faults were established during the Permian – Early Triassic rifting, as indicated by Triassic growth packages in their hanging walls. In contrast, the NE-SW-striking faults are younger, as they show no evidence of Permian – Early Triassic growth, and offset several N-S- and NW-SE-striking faults. Structural analysis show that a new population of NW-SE-striking faults formed in the Lower – Middle Jurassic (inter-rift period) together with reactivation of N-S-striking Permian – Early Triassic faults, indicating a NE-SW inter-rift extension direction. During the Middle Jurassic – Early Cretaceous rifting, faults of all orientations (N-S, NW-SE and NE-SW) were active. However, faults initiated during the Middle Jurassic – Early Cretaceous rifting show mainly N-S orientation, indicating E-W extension during this phase. These observations suggest a reorientation of the stress field from E-W during the Permian – Early Triassic rift phase to NE-SW during inter-rift fault growth and back to E-W during the Middle Jurassic – Early Cretaceous rift phase in the Oseberg area. Hence, the current study demonstrates that rift activity between established rift phases can locally develop faults with new orientations that add to the geometric and kinematic complexity of the final fault population. Highlights: Inter-rift fault activity in the North Sea rift. Significant structural inheritance during second-phase rifting. Local variations in extension during rifting. Various styles of upward propagation during fault reactivation.